Optimalisasi Pemanfaatan Teknologi Augmented Reality Dalam Pengembangan Bahan Ajar Untuk Meningkatkan Kualitas Pembelajaran Sekolah - Rifaldi Herikson; Berta Erwin Slam; Feri Irawan; Nolan Efranda (JPM: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of information technology has driven a transformation in the field of education toward digital and interactive learning. One of the innovations with great potential to support the learning process is Augmented Reality (AR) technology, which can combine virtual elements with the real world in real time to create a more immersive learning experience. This Community Service Program (PKM) was carried out by the Faculty of Engineering and Maritime Technology (FTTK) of Raja Ali Haji Maritime University (UMRAH) at SD Negeri 012 Tanjungpinang Kota, with the aim of improving digital literacy and enhancing teachers’ ability to develop AR-based teaching materials. The methods used included introducing the concept of AR, conducting training on creating interactive learning media using simple devices, and providing assistance in implementing them in the classroom. The results of the program showed an increase in participants’ understanding of AR concepts, basic skills in developing AR-based media, and greater motivation among teachers to integrate technology into the learning process. This activity also raised awareness of the importance of digital innovation in improving the quality of elementary education in Tanjungpinang City. Overall, this training contributed to strengthening an educational ecosystem that is adaptive to technological developments and served as an effective collaboration model between higher education institutions and elementary schools.